2017
DOI: 10.1073/pnas.1705965114
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex modulates posterior alpha oscillations during top-down guided visual perception

Abstract: Conscious visual perception is proposed to arise from the selective synchronization of functionally specialized but widely distributed cortical areas. It has been suggested that different frequency bands index distinct canonical computations. Here, we probed visual perception on a fine-grained temporal scale to study the oscillatory dynamics supporting prefrontal-dependent sensory processing. We tested whether a predictive context that was embedded in a rapid visual stream modulated the perception of a subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 57 publications
16
84
0
Order By: Relevance
“…Since this connectivity effect precedes the presentation of the ambiguous stimulus, an interpretation along the lines of anticipatory predictive processes appears promising (70). Indeed, our findings add to a recent and fastgrowing literature converging towards the idea that low-frequency oscillations carry topdown context (71), category information (72), anticipation (73), and expectations or predictions (74,75). That cognitive, top-down influences come to play leaves open the possibility that the reported connectivity effects are not strictly spontaneous, a nd might be voluntarily driven to some extent.…”
Section: Discussionsupporting
confidence: 66%
“…Since this connectivity effect precedes the presentation of the ambiguous stimulus, an interpretation along the lines of anticipatory predictive processes appears promising (70). Indeed, our findings add to a recent and fastgrowing literature converging towards the idea that low-frequency oscillations carry topdown context (71), category information (72), anticipation (73), and expectations or predictions (74,75). That cognitive, top-down influences come to play leaves open the possibility that the reported connectivity effects are not strictly spontaneous, a nd might be voluntarily driven to some extent.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, it is conceivable that the intact LPFC, alongside with more posterior areas of the frontoparietal control network, suffice to partially modulate posterior alpha during internally directed attention. Previous work has indeed shown that PFC modulation of posterior alpha occurs bilaterally (Helfrich et al, 2017). …”
Section: Discussionmentioning
confidence: 83%
“…For the coregistration of the EEG electrode positions we used, due to the nonavailability of individual anatomic models for our participants, a standard electrode layout, a standard MRI template, and a standard head model (based on the boundary-elements method) from FieldTrip software (Oostenveld et al, 2003). Reconstruction of sources from EEG data based on template anatomical models has been successfully performed by previous studies from our own group and others (for instance, Praamstra et al, 2006; Bendixen et al, 2014; Strauß et al, 2014; Helfrich et al, 2017). …”
Section: Methodsmentioning
confidence: 99%